Recyclable CPL switch regulated by using an applied DC electric field from chiral nematic liquid crystals (N*-LCs). (14th September 2020) - Li, Xiaojing; Shen, Yihao; Liu, Kerui; Quan, Yiwu; Cheng, Yixiang
Abstract : Recyclable CPL response in N*-LCs could be observed by using the applied DC electric field with EPT effect through texture change. This kind of "on–off–on" system based on DC electric field can adjust g em value and direction of CPL in N*-LCs. Abstract : Two pairs of D–A type chiral binaphthyl dyes ( R / S -M1 and R / S -M2 ) as CPL emitters were synthesized and doped into nematic liquid crystals (N-LCs, E7) to form chiral emissive nematic liquid crystals (N*-LCs). The resulting N*-LCs-2 with a smaller dihedral angle of the binaphthyl backbone can emit a strong CPL signal ( g em = −0.83/+0.86) compared with N*-LCs-1 ( g em = −0.20/+0.26) due to the high helix twist power (HTP) in the N*-LCs-2 system. Most importantly, recyclable CPL response behavior in N*-LCs could be observed by using the applied direct current (DC) electric field with the electric phase transition effect (EPT) through texture change from the planar texture into focal conic texture, and then the uniformly-lying helical texture (ULH state). This kind of "on–off–on" system based on DC electric field can adjust the g em value and direction of CPL in N*-LCs. This work can provide a novel strategy for developing a novel CPL device on N*-LCs through the applied DC electric field.